Lipids and C-reactive protein predict anhedonia and reward circuit functional connectivity responses to anti-cytokine and dopaminergic therapies in patients with depression - Aditya Singh; Mandakh Bekhbat; David R. Goldsmith; Ngoc-Anh Le; Evanthia C. Wommack; Zhihao Li; Ebrahim Haroon; Jennifer C. Felger (Comprehensive Psychoneuroendocrinology)
Increased inflammation and associated metabolic disturbances have been shown to affect neurotransmitters and brain circuits, contributing to an immunometabolic phenotype of anhedonic depression. To extend our previous findings on relationships between plasma lipids and antidepressant response to anti-cytokine therapy, we explored in secondary analyses whether lipid-related biomarkers similarly predicted change in anhedonia or functional connectivity (FC) in dopamine-rich corticostriatal reward circuitry in medically-stable, depressed patients with a range of inflammation levels (indexed by plasma C-reactive protein [CRP]) who were administered inflammation-targeted therapies. Relationships were examined between baseline lipids (plasma cholesterols, triglycerides and non-esterified fatty acids) and reduction of anhedonia symptoms in Study 1 (n = 60) after three infusions of infliximab or placebo and change in resting-state FC in Study 2 (n = 31) after acute, within-subject challenge with levodopa (L-DOPA) and placebo. A treatment by inflammation interaction revealed lower anhedonia after infliximab versus placebo (F[1,49] = 5.5, p < 0.05) in patients with, but not without, CRP>3 mg/L (n = 27). A composite score of lipid-related biomarkers (with increasing values reflecting higher concentrations) also precited anhedonia response (post-treatment minus baseline) to infliximab (r = −0.46, p < 0.05) but not placebo (r = 0.14, p = 0.56). Lipid scores similarly predicted CRP-related increases in reward circuit FC after L-DOPA (r = 0.53, p < 0.01) but not placebo (r = 0.20, p = 0.34). Responses to infliximab and L-DOPA were strongest in patients with versus without clinically elevated CRP (>3 mg/L) and/or cholesterol (>150 mg/dL)(p < 0.05). Results highlight a role for dyslipidemia in immunometabolic depression, biomarkers of which, together with CRP, have potential to classify patients indicated for therapies that block inflammation or its effects on neurotransmitters like dopamine.